Genetic analysis of gain yield of IITA and CIMMYT earlymaturing maize inbreds under Strigainfested and lowsoil nitrogen environments - Ifie, B.E.; Badu-Apraku, Baffour; Gracen, V.E.; Danquah, E.Y. (Wiley, 2015)
Breeding maize (Zea mays L.) hybrids resistant to Striga and tolerant to low soil nitrogen (low-N) will reduce grain yield losses due to stresses in West Africa (WA). Studies were conducted to determine if selection for Striga resistance and/or drought tolerance in early-maturing maize populations improved low-N tolerance in hybrids derived from selected inbreds from International Institute of Tropical Agriculture (IITA) and International Centre for Maize and Wheat Improvement (CIMMYT) under Striga-infested, low-N and optimum environments in Nigeria. One hundred and fifty hybrids developed from crosses involving 30 lines using North Carolina Design II plus six checks were evaluated at two locations each under low-N, artificial Striga infestation, and optimum environments for 2 yr. Lines with combined resistance or tolerance to Striga as well as low-N were identified. Striga-resistant– as well as low-N–tolerant hybrids with outstanding performance under both stress environments could be obtained through the accumulation of favorable alleles for resistance or tolerance in both parental lines. Although selection for Striga resistance and/or drought tolerance resulted in improved performance of genotypes under low-N, it is important to test genotypes under low-N to identify those with outstanding performance under the target stress. ENT 11 × TZEI 4 and TZEI 65 × ENT 11 were identified as the most stable and high-yielding hybrids.